Pengaruh Corporate Governance, Ukuran Perusahaan, Dan Thin Capitalization Terhadap Tax Avoidance (Studi Empiris Pada Perusahaan Sektor Energy yang terdaftar di Bursa Efek Indonesia pada tahun 2019-2023) - Syifa Aulia Asykuri; Rudy (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect Independent Commissioners, Audit Committee, Managerial Ownership, Institutional Ownership, Company Size, and Thin Capitalisation on Tax Avoidance. This research includes quantitative research using secondary data obtained from the annual reports of Energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The research method used purposive sampling, and from this method obtained data as many as 10 companies or as much as 50 observation data. The data analysis technique used is panel data regression analysis by selecting regre ssion models, model testing, classical assumption tests and hypothesis analysis using the eviews 10 data processing program. The results showed that partially independent commissioners, audit committees, managerial ownership, institutional ownership, and thin capitalisation had no effect on tax avoidance. While company size has a significant effect on tax avoidance. The results of the study simultaneously show that the variables of independent commissioners, audit committees, managerial ownership, institutional ownership, company size, and Thin Capitalization have an effect on tax avoidance.